Is vegan diet appropriate for competitive artistic gymnasts? - Jakse, B.; Jakse, Ba. (Science of Gymnastics Journal, 2018)
The majority of scientific evidence strongly associates a well-planned vegan diet with health, a successful control of body weight, a preventive measure, and, in some cases, with the termination and the reverse of the most common chronic non-communicable diseases, such as cardiovascular diseases, type 2 diabetes, certain cancers, and some other diseases. Numerous athletes have accepted these findings and adopted this lifestyle choice. Furthermore, the athletes choose well-planned vegan diet with the intention of optimizing their athletic abilities. The position of The British Dietetic Association (BDA) and The Academy of Nutrition and Dietetics (AND) on the vegetarian diet states that well-planned vegetarian diets, including the vegan diet, are healthy and nutritionally adequate and appropriate for all stages of the life cycle, including pregnancy, lactation, infancy, childhood, adolescence and older adulthood. What is more, AND repeats its view from nearly ten years ago on the appropriateness of the vegan diet for the needs of athletes. The aim of this article is to justify the appropriateness of a well-planned vegan diet for the needs for competitive artistic gymnasts and to do so with a relative scientific transparency.